"Such Fictitious Evil Spirits": Adriaan Koerbagh's Rejection of Biblical Demons and Demonic Possession in A Light Shining in Dark Places (1668) - Olmo, Ismael del (Religions, 2019)
This paper traces Adriaan Koerbagh's interpretation of biblical devils and scriptural instances of demonic possession in his 1668 Een Ligt Schijnende in Duystere Plaatsen (A light shining in dark places). Koerbagh's book is a radical exponent of the early Dutch Enlightenment, and its views on demonology are of importance if we want to assess the extent to which traditional scholastic pneumatology was challenged in the second half of the XVIIth century. This paper will also address Thomas Hobbes' positions regarding demons and demonic possession in Leviathan (1651), given that Hobbes' interpretations were fundamental to Koerbagh's own positions. We will focus on the Hobbesian exegetical strategies of etymology, naturalization, and metaphorization, which helped Koerbagh to point at diseases, evil thoughts, figures of speech, or human enemies as plausible explanations for scriptural passages concerning devils and possession. But we will also see that Koerbagh's Cartesian definition of spirits led him to a more radical stance than that of Hobbes: demons do not exist at all. This paper will end by claiming that Koerbagh's interpretation of Christian demonology both as a remnant of Pagan and Jewish superstitions, and a knowledge indifferent to salvation-themselves Hobbesian principles-went hand in hand with his attempt to secularize the biblical text. Thus, the devil, once a part of the sacred truth, could now be seen as a fragment of a human cultural heritage.